MoRoNet a network to strengthen the quality of measles and rubella surveillance in Italy. (30th September 2020) - Magurano, F; Baggieri, M; Bucci, P; D'Ugo, E; Sabbatucci, M; Maraglino, F; Iannazzo, S; Marchi, A; Nicoletti, L
Abstract: Background: Measles is a vaccine-preventable infectious disease and it remains one of the leading causes of infant mortality globally. The World Health Organization (WHO) has adopted the goal of eliminating measles and rubella. Detection and control of communicable diseases would not be possible without accurate laboratory results regarding when and where a particular disease circulates. Methods: WHO/Europe therefore works with all Member States to steadily improve the quality of the laboratory data in order to determine the Region's progress towards measles and rubella elimination. For this purpose coordinates the European Measles and Rubella Laboratory Network (MR LabNet). National labs in this network undergoes regular external quality assessment through an annual accreditation programme. Results: In Italy, a Sub-national Reference Laboratories Network for measles and rubella (MoRoNET) has been developed since March 2017 and currently includes 15 laboratories. MoRoNet was developed following the indications of the MR LabNet. It is accreditate, coordinated and supervised by the National Reference Laboratory. Conclusions: Strengthening the role of national laboratories in overseeing the performance of subnational laboratories has become a critical need in order to properly monitor the Region's measles and rubella elimination efforts. MoRoNet permits to Italy to develop a country-specific work plan for establishing national networks and oversight mechanism, including preliminary monitoring and evaluation indicators compliant with MR LabNet standards. This is very significant not only to optimize the participation in national and regional processes to verify disease elimination, but also to strengthen the quality of vaccine-preventable disease surveillance. MoRoNet Group: A Amendola; F Baldanti; MR Capobianchi; M Chironna; MG Cusi; P D'Agaro; P Lanzafame; T Lazzarotto; K Marinelli; A Orsi; E Pagani; G Palù; F Pittaluga, A Sacchi; F Tramuto. Key messages: MoRoNet has permitted to Italy to develop a country-specific work plan for establishing national networks and oversight mechanism, compliant with WHO MR LabNet standards. MoRoNet network has permitted to optimize the participation in processes to verify disease elimination, but also to strengthen the quality of vaccine-preventable disease surveillance.